Protection and Concervation of Agia Eirini Gorge Geotope, West of the Samaria National Park, Western Crete - Bizoura, A.; Manutsoglou, E. (Bulletin of the Geological Society of Greece, 2012)
The unique in beauty and scientific interest geotope of Agia Eirini gorge is located at the western side of the White Mountains, in the Prefectural Administration of Chania. It is part of the European path E4, has a length of 7,5 kilometers and its northern entry is located at Agia Eirini village, 43 km far from Chania. It is part of the “Lefka Ori” Natura 2000 region (Code GR 4340008), part of the Samaria National Park and α Wild Life Shelter. The gorge crosses the metamorphic carbonate rocks of the Trypali Unit (age up to Middle Triassic) and the units of the Phyllite Nappe. The gorge represents a fault zone with a NNE – SSW direction, following the general direction of the large faults that cut the Mesozoic formations of the region. Along this path a lot of tectonic features can be regarded and studied, so the gorge can be characterized as a natural laboratory for the understanding of the terms fault and fault zone. In this study, using GIS, an information system for the gorge of Agia Eirini is organized and the combination of thematic maps revealed a delimitation problem of the protected area.